Knowledge Study, Income Level and Socio-Culture of the Nutritional Status of toddler - Marniati Marniati; Enda Silvia Putri; Susy Sriwahyuni; Khairunnas Khairunnas; Maiza Duana (Journal of Nutrition Science, 2020)
Toddler Nutrition Status Is a state of balance or manifestation of nutrition in the form of certain variables. The high incidence of malnutrition in Suka Makmue Subdistrict is centered as the main target in improving nutrition. The objective is to analyze the Knowledge Study of Income and Social Culture Level of Toddler Nutrition status in Blang Muling Village, Suka Makmue Subdistrict, Nagan Raya Regency. This type of research is Analytical Surveys with cross-sectional approach. The total number of samples is 33 mothers of toddlers. Univariate and Bivariate analyzes were further tested with Chi Square. The results after a deeper study of the three variables have an influence on the nutritional status of children under five namely Knowledge (Pvalue 0,000 <α 0.05), income level (Pvalue 0.001 <α 0.05), and socio-cultural (Pvalue 0.003 <α 0.05) . Suggestion Health workers should be more active in delivering information about the importance of the nutritional status of children under five.